2007
DOI: 10.1074/jbc.m703895200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Distal S6 Hydrophobic Residues in the Voltage-dependent Gating of CaV2.3 Channels

Abstract: The hydrophobic locus VAVIM is conserved in the S6 transmembrane segment of domain IV (IVS6) in Ca V 1 and Ca V 2 families. Herein we show that glycine substitution of the VAVIM motif in Ca V 2.3 produced whole cell currents with inactivation kinetics that were either slower (A1719G ≈ V1720G), similar (V1718G), or faster (I1721G ≈ M1722G) than the wild-type channel. The fast kinetics of I1721G were observed with a ≈؉10 mV shift in its voltage dependence of activation (E 0.5,act ). In contrast, the slow kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 53 publications
3
39
0
Order By: Relevance
“…Mutations within IIS6 were found to impact most significantly on the activation gating of Ca V 2.3. In particular, I701G shifted by Ϫ35 mV the voltage dependence of activation while slowing down inactivation and deactivation kinetics (20). These data indicated that IIS6 plays a unique role in the channel equilibrium between the closed and the open state(s) in Ca V 2.3.…”
Section: ؊1mentioning
confidence: 74%
See 4 more Smart Citations
“…Mutations within IIS6 were found to impact most significantly on the activation gating of Ca V 2.3. In particular, I701G shifted by Ϫ35 mV the voltage dependence of activation while slowing down inactivation and deactivation kinetics (20). These data indicated that IIS6 plays a unique role in the channel equilibrium between the closed and the open state(s) in Ca V 2.3.…”
Section: ؊1mentioning
confidence: 74%
“…In contrast to K V channels, Ca V channels are structurally asymmetrical with four distinct albeit homologous S4S5 linkers and four distinct S6 helices. We have already shown that glycine substitutions in the distal S6 regions of domains I, II, III, and IV altered the relative stability between the open and closed states (20). Mutations within IIS6 were found to impact most significantly on the activation gating of Ca V 2.3.…”
Section: ؊1mentioning
confidence: 99%
See 3 more Smart Citations